Synthesis, confirmation based on in vitro and in silico study of thiadiazole-based thiazolidinone scaffolds: An approach toward Covid-19 - Shoaib Khan; Rafaqat Hussain; Yousaf Khan; Tayyiaba Iqbal; Mohammad Shahidul Islam; Tahani Mazyad Almutairi (Results in Chemistry, 2024)
Coronavirus disease (COVID-19), an infectious disease caused by a newly discovered Coronavirus (severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) was targeted in the current research study. Different hybrid thiadiazole based thiazolidinone derivatives were designed and successfully synthesized. Structural validation of novel compounds was achieved via spectroscopy by employing 1HNMR, 13CNMR, HREI-MS. All the synthesized compounds were biologically evaluated to study their potential to inhibit the main protease of SARS-CoV-2. The SAR data revealed that among the synthesized thiadiazole-based thiazolidinone derivatives showed significant inhibitory profile against the targeted enzymes. Different substituted compounds 1 (IC50 = 0.10 µM), 2 (IC50 = 1.43 µM), 4 (IC50 = 2.25 µM), 5 (IC50 = 24.56 µM), 6 (IC50 = 26.47 µM), and 8 (IC50 = 19.59 µM), were found with excellent potentials, even more potent than its standard GC-376 drug (IC50 = 0.439 µM). Among the potent candidates of the series, compound 1 bearing CF3 at meta and NO2 at ortho position exhibited the top ranking potential and emerged as the excellent inhibitor of protease of SARS-CoV-2. Furthermore, these potent analogues were subjected to molecular docking study in order to explore their bonding interactions with active sites of SARS-CoV-2 3CL protease. This study was also enriched with ADME analysis to evaluate drug-likeness of lead compounds of the series.